Dopaminergic modulation of synaptic transmission and neuronal activity patterns in the zebrafish homolog of olfactory cortex - Zhang Schärer, Yan-Ping; Shum, Jennifer; Moressis, Anastasios; Friedrich, Rainer W. (Frontiers in Neural Circuits, 2012)
Dopamine (DA) is an important modulator of synaptic transmission and plasticity that is causally involved in fundamental brain functions and dysfunctions. We examined the dopaminergic modulation of synaptic transmission and sensory responses in telencephalic area Dp of zebrafish, the homolog of olfactory cortex. By combining anatomical tracing and immunohistochemistry, we detected no DA neurons in Dp itself but long-range dopaminergic input from multiple other brain areas. Whole-cell recordings revealed no obvious effects of DA on membrane potential or input resistance in the majority of Dp neurons. Electrical stimulation of the olfactory tracts produced a complex sequence of synaptic currents in Dp neurons. DA selectively decreased inhibitory currents with little or no effect on excitatory components. Multiphoton calcium imaging showed that population responses of Dp neurons to olfactory tract stimulation or odor application were enhanced by DA, consistent with its effect on inhibitory synaptic transmission. These effects of DA were blocked by an antagonist of D2-like receptors. DA therefore disinhibits and reorganizes sensory responses in Dp. This modulation may affect sensory perception and could be involved in the experience-dependent modification of odor representations.